Incorporation and Productivity - Robert J. Barro; Brian Wheaton (Center for Economic Studies and ifo Institute (CESifo), 2019)
Corporate versus pass-through status trades off productivity benefits (related to perpetual identity, limited liability, public trading, and earnings retention) against tax wedges, estimated from U.S. federal taxes on corporate profits, dividends, and partnership income. In regressions, C-corporate economic shares decline with the wedge and exhibit negative trends, which we relate to legal changes for LLCs since the late 1980s. A calibrated model, fit to observed total factor productivity (TFP) and corporate shares of economic activity, implies that, for 1958-2013, the declining wedge and gap between corporate and pass-through productivity contributed 0.37% per year out of the total TFP growth rate of 1.09% per year. From 1994 to 2004, the TFP growth rate was unusually high—2.00% per year—and the contribution from the falling productivity gap was unusually large—0.77% per year.
Keywords: 330